Beyond global nodes and economic indicators in the evaluation of the world-system of cities - Diez-Pisonero, Roberto; Gago-García, Cándida; Córdoba Ordóñez, Juan A. (DIE ERDE – Journal of the Geographical Society of Berlin, 2020)
The paper aims to look at the organisation of the world-urban system. It proposes an integrated explorative approach which, in addition to considering economic-production type indicators, includes others that can reflect a complex approach to functional and geographic specialisation. Methodologically, the comparative analysis of three synthetic indices through a cluster analysis allows for the multifunctional representation of the world-urban system, in which other centralities and cities excluded from other rankings are considered. The first index is taken from the proposal by the GaWC (Global and World Cities Research Network). The second relates to cultural services and some of the knowledgeintensive activities. The third includes variables related to mobility, more specifically air transport. The comparison of functions, as revealed by the indices, can provide information about how cities work in the world context. The analysis allows for the identification of a group of prominent multifunctional cities at the top, and a large group of less prominent and specialised cities underneath.